Meeting the Challenge of Burnout - (:unkn) unknown (My University, 2025)
In this lecture, Professor Christina Maslach expounds on the occupational phenomenon of burnout that results from chronic workplace stressors, the different ways in which burnout has been addressed, and the key to improving the match between people and their jobs to enable people to work smarter and to thrive
Keywords: Burnout